Florida's Total Maximum Daily Load Program After Seven Years of Implementation - Mark W. Clark; William F. DeBusk (EDIS)
SL270, a 3-page fact sheet by Mark W. Clark and William F. DeBusk, describes what a TMDL is, implementation of the program in Florida, contaminants triggering the process, and possible reclassification of state water body “designated uses.” Published by the UF Department of Soil and Water Science, October 2008.